Short-Term Changes in Fertility Attributes and Soil Organic Matter Caused by the Addition of EM Bokashis in Two Tropical Soils - Carlos Eduardo Pacheco Lima; Mariana Rodrigues Fontenelle; Luciana Rodrigues Borba Silva; Daiane Costa Soares; Antônio Williams Moita; Daniel Basílio Zandonadi; Ronessa Bartolomeu Souza; Carlos Alberto Lopes (International Journal of Agronomy)
The present work aimed to evaluate the behavior of ten fertility attributes of soil organic matter physical fractions and total organic carbon upon addition of three EM Bokashis to a Rhodic Ferralsol (FRr) and a Dystric Cambisol (CMd). An experiment was carried out in greenhouse in which the soils were placed into plastic trays and cultivated with tomato. A completely randomized design was used with four repetitions and factorial scheme of 2 × 3 + 2, consisting of two soils (FRr and CMd), three EM Bokashis (Poultry Manure Bokashi (BPM); CNPH Bokashi (BC); and Cattle Manure Bokashi (BCM)), and two controls (both soils without addition of Bokashi). The following fertility attributes were evaluated: pH, Ca2+, Mg2+, K+, Na+, P, SB, H + Al, CEC, and V. Particulate organic carbon (POC) and mineral-associated organic carbon (MOC) and total organic carbon (TOC) were also investigated. Finally, the Principal Component Analysis was conducted in order to identify possible patterns related to soils when fertilized with EM Bokashi. The addition of EM Bokashi increased the soil fertility and contents of POC. Different EM Bokashi presents distinguished effects on each soil. The PCA suggests that BPM presents higher capacity to modify the analyzed chemical attributes.